A Computational Design Framework Supporting Human Interaction with Environmentally-Responsive Building Envelopes. (March 2015) - Krietemeyer, Bess; Andow, Brandon; Dyson, Anna
Emerging materials present opportunities to fundamentally shift current expectations of dynamic building envelope functionality towards systems that can respond to occupant needs while meeting the energy demands of buildings. In order to assess the environmental, social, and architectural opportunities that are increasing with responsive building envelopes, new tools are needed to simulate their multi-performance capabilities. This paper describes a computational design framework to support human interaction with environmentally-responsive electroactive dynamic daylighting systems. The objective is to develop algorithms for variable solar control and visible transmittance that simultaneously address occupant preferences for visual effects and interaction. Results demonstrate that energy performance and user satisfaction are not mutually exclusive and can be co-optimized. The effectiveness and limitations of the computational framework in assessing strategies to balance environmental performance and human interaction are discussed. Conclusions present areas of ongoing work that integrate multi-user interactions and immersive visualization techniques with multiscalar energy modeling tools.